KEWENANGAN PRESIDEN DALAM MEMBENTUK UNIT KERJA PRESIDEN - Purnamawati, Evi (Solusi, 2020)
The constitution is supreme because it is assumed as a form of agreement of all people. Indonesia adheres to the supreme constitution and the understanding of democracy, so that every policy whether it is a product of legislation or other political policies must be in accordance with the values ​​of society or in accordance with the wishes of its people. The authority of the President as the holder of government power is not unlimited power, but has guiding principles in making specific policies regarding the formation of the Presidential Work Unit. These rules must be in line with the constitution and democracy (constitutional democracy). Institutional relations between the President's Work Unit for Development Supervision and Control with the Ministry of State, Cabinet Secretariat as well as between the Legal Mafia Eradication Task Force and law enforcement agencies such as the Corruption Eradication Commission, the Police, and the Prosecutors' Office, have the potential for overlapping authorities in the practice of implementing government and law enforcement.